2021
DOI: 10.3389/fpsyg.2020.577942
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Infection Risk and Depressive Symptoms Among Young Adults During Quarantine: The Moderating Role of Grit and Social Support

Abstract: Prior research has demonstrated that the adverse consequences of the coronavirus disease 2019 (COVID-19) pandemic may go beyond its economic hardships and physical health concerns, having a significant influence on psychological distress for individuals under quarantine. Nevertheless, relatively little attention has been paid to exploring the risk and protective factors in the link between COVID-19 infection risk and psychological distress among young adults. Following a socioecological framework, the current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
2
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 79 publications
(119 reference statements)
3
26
2
2
Order By: Relevance
“…National and international surveys have revealed that 1 in 2 young adults (aged 18-29 years) are subject to depression and anxiety and 1 in 6 are probably affected [21]. These results are in line with many studies on the current pandemic revealing higher psychological distress and depressive symptoms, particularly among young adults [22,23].…”
Section: Introductionsupporting
confidence: 76%
“…National and international surveys have revealed that 1 in 2 young adults (aged 18-29 years) are subject to depression and anxiety and 1 in 6 are probably affected [21]. These results are in line with many studies on the current pandemic revealing higher psychological distress and depressive symptoms, particularly among young adults [22,23].…”
Section: Introductionsupporting
confidence: 76%
“…Specifically, this study will discriminate the different perceived levels of social support among students and its impacts on students' coping tendency, and then further investigate the effect of social support-coping mode on students' mental health. The results of previous social support theory-related studies show that social support, as an important environmental resource for individuals in social life, is closely related to the control and prevention of negative emotions; good social support can provide protection for individuals under stress and has a generally beneficial effect on maintaining the health and stabilizing the mood of individuals (MartĂ­n-Albo et al, 2015 ; Hou et al, 2020 ). The same stressful situation can have different impacts on different individuals (Guay et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these training programs, workplace incivility scholars suggest that service organizations should give FSEs a short break after difficult customer encounters (Kim and Qu 2019 ; Sliter et al 2010 ) since it would enable them to recover from stress and recharge their resources. At last, in the light of the findings that social support can alleviate COVID-related stress and anxiety and fortify employees’ coping capabilities (Charoensukmongkol and Phungsoonthorn 2020 ; Hou et al 2020 ), service organizations need to provide managerial and peer support for FSEs who are exposed to interpersonal stressors amid the pandemic.…”
Section: Discussionmentioning
confidence: 99%